58.2k views
0 votes
Convert the vertex form into standard form.


y(x-2)^(2) + 8\\\\
so
y = x^2 - ? + ?

User JaakkoK
by
6.0k points

2 Answers

2 votes

Answer:

y = x²-4x+12

Explanation:

We have given an equation which is in vertex form.

y = (x-2)²+8

We have to convert above equation into standard form.

Standard form of equation is

y = ax²+bx+c

Expanding the square term by using following formula,

(a+b)² = a²+2ab+b²

y = x²-4x+4+8

Adding like terms, we have

y = x²-4x+12 which is the answer.

User Jschnasse
by
4.7k points
4 votes

Answer:

y = x² - 4x + 12

Explanation:

Parabolas have two equation forms; namely the standard and vertex forms.

In the standard form, y = ax2 + bx + c, where a, b and c are constants.

A parabolic equation resembles a classic quadratic equation.

Therefore;

y= (x-2)² + 8

we expand (x-2)²

(x-2)² = x² -4x +4

Thus;

y = x² -4x +4 + 8; simplify;

y = x² - 4x + 12

User Han Che
by
5.6k points